LEARNING MODEL BASED ON GEOSFER PHENOMENA FOR UNDERSTANDING THE DISASTER CONCEPT - Ningrum, Epon (Jurnal Pendidikan Geografi Gea, 2017)
This study focused on the utilization of the geosphere phenomenon in learning geography for understanding the concept of disaster. Geosphere phenomenon based learning are formulated based on a literature review for obtain theoretical foundations that have the basic assumptions, descriptions, and basic concepts. Geosphere phenomenon based learning consists of seven steps activity that is (1) identification of basic competence; (2) identification of the geosphere phenomenon which has a carrying capacity; (3) identification of the ability of teachers; (4) identification of the characteristics of the students; (5) to formulate lesson plans; (6) implementing the learning activities; and (7) follow-up. Meanwhile, the learning process through four steps, that is (1) The concept exploration phase; (2) the stage of introduction of the concept; (3) the stage of development of the concept; and (4) the stage of concept application. Understanding the concept of a hierarchy of integrated disaster include: (1) the level of concrete); (2) the level of identity; (3) the level of classification; and (4) a formal level. The effectiveness of the geosphere phenomenon based learning teachers ability methodologically necessary and substantial.